Impact of age on semen parameters in male partners of infertile couples in a rural tertiary care center of central India: A cross-sectional study - Naina Kumar; Amit K Singh; Ajay R Choudhari (Shahid Sadoughi University of Medical Sciences, 2017)
Background: High rates of sub-fertility and adverse pregnancy outcomes were seen after age 40. In contrast to oogenesis, spermatogenesis continues in elderly men. Objective: To retrospectively study the impact of aging on semen parameters in male partners of infertile couples in the rural area of developing country over 10 years and to find out whether aging affects male factor fertility and various semen parameters in this part of developing country. Materials and Methods: In this cross sectional study, the laboratory semen analysis records of 1219 male partners of infertile couples of a rural tertiary care center of Central India in a 10-year period from January 2005 to December 2014 were evaluated into 5 groups based on men age: Group 1: 21-28 yr (n=57); group 2: 29-35 yr (n=450); group 3: 36-42 yr (n=532); group 4: 43-49 yr (n=165), and group 5: 50-60 yr (n=15). Evaluation of all semen parameters were done according to WHO standard criteria (1999). Results: The analysis of semen records revealed the significant negative association of semen volume, total sperm count, sperm motility, and morphology with age. There was a significant fall in total sperm count, sperm motility, and morphology after the age of 35 yr. Conclusion: Age has significant negative effect on semen volume, total sperm count, and sperm motility and morphology in this region of India.